How Does Diabetes Accelerate Normal Aging? An Examination of ADL, IADL, and Mobility Disability in Middle-aged and Older Adults With and Without Diabetes. (December 2021) - Tsai, Yi-Hsuan; Chuang, Li-Lun; Lee, Yau-Jiunn; Chiu, Ching-Ju
Abstract: Objectives: To build an age norm to quantify and compare the different progression rates of disability in people with and without diabetes. Methods: Data were extracted from 5, 131 adults aged 50 and older from the Taiwan Longitudinal Study in Aging (TLSA) conducted in 1996. Using multilevel mixed models, the disabilities were measured in 1999, 2003, and 2007. Results: Diabetes accelerated the occurrence and progression of disabilities during aging. Participants with diabetes developed to mobility, IADL, and ADL at the age of 55, near the age of 60, and near the age of 70, respectively. Diabetes accelerated the onset of disabilities of mobility by 3 years, IADL by 7 years, and ADL by 11 years. In the fully adjusted model, diabetes remains a robust predictor for levels of disability (MobilityβDM  = 1.668, p  < 0.001, IADLβDM  = 1.031, p  < 0.001) (IADβDM  = 0.690, p  < 0.001), and rate of change for developing mobility disability (MobilityβDM*age  = 0.088, p  < 0.001). Conclusions: This study showed that diabetes accelerated the occurrence and progression of disabilities starting in middle age. A three to eleven years of acceleration on disability development on mobility, IADL, and ADL was observed.